Innovative geocomposite for dredged sediments depollution. Issue 1 (1st October 2022) - Forogo, B W; Stolz, G; Coquery, M; Bonelli, S; Chaouch, N; Touze, N
Abstract: In France, sediments from river dredging are considered as waste. Without any special treatment, they must be stored in landfills. The dredged sediments of our area of study (North of France) are polluted with trace metals (antimony and zinc are above the French regulation threshold). The main objective of this study is to develop a new method of active depollution and dewatering treatment in order to enable the reuse of treated sediments. This treatment is carried out through ponds equipped with innovative geocomposite. This innovative geocomposite has two typical passive functions (filtration and drainage). In addition, it is functionalized by an innovative electrokinetic technology to confer it active roles (depollution and dewatering). Electrokinetic consists in applying a difference of electrical potential to a porous medium. We present here the results of a preliminary laboratory study that simulates this new method on a short-term (3 weeks) experiment. The results show that the electrokinetic treatment has an impact on the chemical and physical properties of sediments. The treatment reduces by 50% the concentration of zinc in the leachate after lixiviation.